Antibacterial and Antifungal of β-sitosterol Isolated from Hydroid Aglaophenia cupressina Lamoureoux Against Xanthomonas campestris and Fusarium oxysporum - Johannes, Eva; Manguntungi, Baso; Tuwo, Mustika; Litaay, Magdalena; Mustopa, Apon Zaenal; Vanggy, Leggina Rezzy (Marine Science Department Diponegoro University, 2025)
This study aimed to isolate and characterize β-sitosterol from the marine hydroid Aglaophenia cupressina Lamoureoux and evaluate its antibacterial and antifungal activities against Xanthomonas campestris and Fusarium oxysporum. β-Sitosterol was extracted, purified, and identified using spectroscopic techniques, including infrared and nuclear magnetic resonance spectroscopy. Antimicrobial activity was assessed through agar diffusion method to determine its inhibitory effects on bacterial and fungal growth at varying concentrations. β-sitosterol is a crystalline compound, with a melting point of 138-139°C, consistent with the reported range for pure β-sitosterol, indicating high purity. Infrared (IR) spectroscopy revealed key functional groups, including a hydroxyl group at 3433 cm⁻¹, C-O stretching at 1050 cm⁻¹, and aliphatic hydrocarbon chain vibrations at 2956, 2938, and 2869 cm⁻¹. The C=C stretching at 1634 cm⁻¹ and C-H bending at 1465 cm⁻¹ confirmed its unsaturated sterol structure. ¹H NMR spectroscopy further confirmed the structure with characteristic methyl and olefinic proton signals. The antibacterial activity of β-sitosterol against Xanthomonas campestris showed a concentration- and time-dependent effect, with the highest efficacy observed at 60 ppm, demonstrating potential as a natural antibacterial agent. Additionally, its antifungal activity against Fusarium oxysporum revealed both fungistatic and fungicidal effects, with lower concentrations exhibiting fungistatic behavior and higher concentrations displaying fungicidal activity, thereby offering versatility for both fungal inhibition and eradication. This dual action, combined with its well-characterized molecular structure, positions β-sitosterol as a promising candidate for further development as an antimicrobial compound. The findings underscore the accuracy of the identification process and highlight β-sitosterol's potential in pharmaceutical and agricultural applications, particularly in combating bacterial and fungal infections.